2014
DOI: 10.1097/prs.0000000000000429
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Dupuytren Disease in Fingers

Abstract: Risk, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…Gebereegziabher et al are the first to describe a substantial series of 75 Ethiopian cases of DD originating from various tribes living in various parts of the country, but seen in one hospital in Addis Ababa over the course of 2 years. The age distribution, as well as the phenotypical characteristics of DD in these cases are, in general, similar to those of a previously described (Caucasian) series (Lanting et al, 2014), except for the underrepresentation of symptoms in the left hand. Of note is the relatively high prevalence of hypertension found in this series, which has not been reported in Caucasian series, but has in a nation-wide population-based study in Taiwan (Yeh et al, 2015).…”
supporting
confidence: 85%
“…Gebereegziabher et al are the first to describe a substantial series of 75 Ethiopian cases of DD originating from various tribes living in various parts of the country, but seen in one hospital in Addis Ababa over the course of 2 years. The age distribution, as well as the phenotypical characteristics of DD in these cases are, in general, similar to those of a previously described (Caucasian) series (Lanting et al, 2014), except for the underrepresentation of symptoms in the left hand. Of note is the relatively high prevalence of hypertension found in this series, which has not been reported in Caucasian series, but has in a nation-wide population-based study in Taiwan (Yeh et al, 2015).…”
supporting
confidence: 85%
“…[ 2 ] Myofibroblasts differentiated from normal fibroblasts have been considered a cause of the flexion contractures. Because clinical investigations of Dupuytren disease have demonstrated a strong, unexplained predominance in men, with a male:female ratio of about 6:1 among Dupuytren disease patients, [ 3 ] and a predominance in the ulnar rays, that is, the fourth and fifth digits, [ 4 ] we developed a hypothesis that myofibroblast metabolism may be regulated by endogenous androgenic male hormones, which is also supported by the previous reports. Pagnotta et al [ 5 , 6 ] have shown that the palmar fascia of Dupuytren disease had higher expression of androgenic receptors than in those without Dupuytren disease, and that cultured fibroblasts from patients with Dupuytren disease were significantly differentiated into myofibroblasts by stimulation with androgens.…”
Section: Introductionsupporting
confidence: 67%
“…Nodules can present in both the palm and fingers. The ring finger is most often affected, and then, in order of frequency, the small finger, thumb, middle finger, and index finger [ 2 ]. DD is commonly bilateral, and it can become both a physically and a psychosocially disabling condition that significantly affects healthcare resources [ 3 ].…”
Section: Introductionmentioning
confidence: 99%